A phase II study of adjuvant gemcitabine plus docetaxel followed by concurrent chemoradation in resected pancreaticobiliary carcinoma. Issue 7 (July 2015) - Cho, May; Wang‐Gillam, Andrea; Myerson, Robert; Gao, Feng; Strasberg, Steven; Picus, Joel; Sorscher, Steven; Fournier, Chloe; Nagaraj, Gayathri; Parikh, Parag; Suresh, Rama; Linehan, David; et al.
Abstract: Objectives: Adjuvant gemcitabine with or without chemoradiation is a standard therapeutic option for patients with resected pancreatic cancer. The feasibility and toxicity of gemcitabine with docetaxel before and after 5‐fluorouracil (5FU)‐based chemoradiation in the adjuvant pancreatic and biliary cancer setting were investigated. Methods: After a curative‐intent resection, eligible patients with pancreaticobiliary cancers were treated with two cycles of gemcitabine and docetaxel followed by 5FU‐based chemoradiation. Four weeks after completing chemoradiation, two cycles of gemcitabine and docetaxel were administered. The primary endpoint was the incidence of severe toxicities. Secondary endpoints included disease‐free survival (DFS) and overall survival (OS). Results: Fifty patients with pancreaticobiliary cancers were enrolled. Twenty‐nine patients had pancreatic cancer whereas 21 patients had biliary tract or ampullary cancers. There was one death as a result of pneumonia, and 15% of patients experienced grade 3 or greater non‐haematological toxicities. The median DFS and OS for patients with pancreatic cancer were 9.6 and 17 months, respectively, and for those with resected biliary tract cancer were 12 and 23 months, respectively. Conclusions: This combination of gemcitabine and docetaxel with chemoradiation is feasible and tolerable in the adjuvant setting. Future studies utilizing a different gemcitabine/taxane combination and schedule may be appropriate in the adjuvant treatment of both pancreatic cancer and biliary tumours.